Role induced bias in court: An experimental analysis - Andreas Glöckner; Christoph Engel (Max Planck Institute for Research on Collective Goods, 2010)
Criminal procedure is organized as a tournament with predefined roles. We show that assuming the role of a defense counsel or prosecutor leads to role induced bias even if people are highly motivated to give unbiased judgments. In line with parallel constraint satisfaction models for legal decision making, findings indicate that role induced bias is driven by coherence effects (Simon, 2004), that is, systematic information distortions in support of the favored option. These distortions seem to stabilize interpretations, and people do not correct for this bias. Implications for legal procedure are briefly discussed.
Keywords: D81; K42; C91; K14; 330; parallel constraint satisfaction; intuition; biases; legal decision making; Strafverfahren; Rechtsprechung; Soziale Rolle; Bias; Test